Research on the Challenges and Optimizations in the Development of Carbon Futures Market - Tang Ziyi (SHS Web of Conferences, 2025)
As global warming increased, countries set carbon neutrality targets, which contributed to the rapid development of financial carbon markets. As an important part of carbon financial instruments, the carbon futures market has important functions in pricing and risk management and is of great importance for achieving emission reduction targets. The market also faces challenges, including market fragmentation and political uncertainty. This article discusses the current situation and proposals to optimize the global carbon futures market. First, analyze its development process and market participants and transaction data; then study its function in pricing; then identify shortcomings such as market segmentation and technical problems; and finally offer solutions such as increased regulatory transparency and increased technical support. This study contains practical and feasible proposals for relevant participants that will help promote healthy market development and will be of leading importance for future research.